Incidence of allergy and allergy symptoms among workers exposed to laboratory animals. Issue 11 (18th October 2005) - Elliott, L; Heederik, D; Marshall, S; Peden, D; Loomis, D
Abstract : Background and Aims: Few studies have described relations between exposure to laboratory animals and the incidence of laboratory animal allergy (LAA). Studies that have found exposure-response relations have been cross sectional in design or have focused on exposure to rats and mice. This study used longitudinal data collected over a 12 year period to describe the relations between indices of exposure to laboratory animals and the development of LAA and LAA symptoms. Methods: Data were obtained from questionnaires and serological laboratory results from a dynamic cohort of workers exposed to a variety of laboratory animals in a pharmaceutical manufacturing company. Poisson regression was used to model the incidence rate ratios of species specific and general LAA and LAA symptoms at different levels of exposure. Results: The 12 year incidence rates of LAA symptoms and LAA for all workers were 2.26 (95% CI 1.61 to 2.91) and 1.32 (95% CI 0.76 to 1.87) per 100 person-years, respectively. Higher rate ratios were seen with increasing reported hours of exposure to tasks that required working with animal cages or with many animals at one time. The most common symptoms were related to rhinitis rather than to asthma. Conclusions: This study suggests that the risk of LAA increases with duration of exposure to animals and work in animal related tasks. Incidence might be reduced by limiting hours per week of exposure to laboratory animals.